Osteoarthritis Affects Mammalian Oogenesis: Effects of Collagenase-Induced Osteoarthritis on Oocyte Cytoskeleton in a Mouse Model - Anton Ivanov Kolarov; Irina Valcheva Chakarova; Valentina Prodanova Hadzhinesheva; Venera Pantaleeva Nikolova; Stefka Metodieva Delimitreva; Maya Dyankova Markova; Ralitsa Stefanova Zhivkova (Hindawi Limited, 2021)
Known as a degenerative joint disorder of advanced age affecting predominantly females, osteoarthritis can develop in younger and actively working people because of activities involving loading and injuries of joints. Collagenase-induced osteoarthritis (CIOA) in a mouse model allowed us to investigate for the first time its effects on key cytoskeletal structures (meiotic spindles and actin distribution) of ovulated mouse oocytes. Their meiotic spindles, actin caps, and chromatin were analyzed by immunofluorescence. A total of 193 oocytes from mice with CIOA and 209 from control animals were obtained, almost all in metaphase I (M I) or metaphase II (MII). The maturation rate was lower in CIOA (26.42% M II) than in controls (55.50% M II). CIOA oocytes had significantly larger spindles (average 37 μm versus 25 μm in controls, p<0.001), with a proportion of large spindles more than 64% in CIOA versus up to 15% in controls (p<0.001). Meiotic spindles were wider in 68.35% M I and 54.90% M II of CIOA oocytes (mean 18.04 μm M I and 17.34 μm M II versus controls: 11.64 μm M I and 12.64 μm M II), and their poles were approximately two times broader (mean 6.9 μm) in CIOA than in controls (3.6 μm). CIOA oocytes often contained disoriented microtubules. Actin cap was visible in over 91% of controls and less than 20% of CIOA oocytes. Many CIOA oocytes without an actin cap had a nonpolarized thick peripheral actin ring (61.87% of M I and 52.94% of M II). Chromosome alignment was normal in more than 82% in both groups. In conclusion, CIOA affects the cytoskeleton of ovulated mouse oocytes-meiotic spindles are longer and wider, their poles are broader and with disorganized fibers, and the actin cap is replaced by a broad nonpolarized ring. Nevertheless, meiotic spindles were successfully formed in CIOA oocytes and, even when abnormal, allowed correct alignment of chromosomes.